Managing a Rare Major Aortopulmonary Collaterals with Single Ventricle Physiology through Coiling and Cavopulmonary Shunt in a Single Hybrid Setting: A Case Report - Yadav, Samir Kumar; Bhattarai, Anil; Baral, Ravi; Khakural, Prabhat (Journal of Institute of Medicine Nepal, 2025)
We report a case of a 15-year-old female with single ventricle physiology, double outlet right ventricle, situs inversus, and major aortopulmonary collateral arteries (MAPCAs), treated in a single hybrid setting with endovascular coiling of nonessential MAPCAs and Bidirectional Glenn (BDG) procedure. Current guidelines recommend optimizing the pulmonary vascular bed through unifocalization of essential MAPCAs and embolization of nonessential MAPCAs to achieve Cavo pulmonary anastomosis, often via single- or multi-staged approaches. This case demonstrates the feasibility of a hybrid approach for complex CHDs.